Iowa RBA, June 19-20,1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for June 19-20, 1995. Highlights of the update include sightings of the continued presence of a Prairie Warbler, two Yellow-crowned Night Herons, Forster's and Black Terns, Bonaparte's Gull, Gadwall and a Northern Shoveler. Epson - sheet feed/flatbed